2019
DOI: 10.1038/s41598-019-44013-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and free energy landscape of novel mutations in ribosomal protein S1 (rpsA) associated with pyrazinamide resistance

Abstract: Resistance to key first-line drugs is a major hurdle to achieve the global end tuberculosis (TB) targets. A prodrug, pyrazinamide (PZA) is the only drug, effective in latent TB, recommended in drug resistance and susceptible Mycobacterium tuberculosis (MTB) isolates. The prodrug conversion into active form, pyrazinoic acid (POA), required the activity of pncA gene encoded pyrazinamidase (PZase). Although pncA mutations have been commonly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 82 publications
(71 reference statements)
5
40
0
1
Order By: Relevance
“…The binding free energy demonstrated that N-NTD exhibited a decreased affinity toward RNA in MTs T57, H59, S105A, R107A, G170, F171, and Y172. Since these methods are widely used by different studies to understand the impact of mutations [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…The binding free energy demonstrated that N-NTD exhibited a decreased affinity toward RNA in MTs T57, H59, S105A, R107A, G170, F171, and Y172. Since these methods are widely used by different studies to understand the impact of mutations [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…In silico, methods to predict structural implications of mutations will be beneficial in understanding mechanisms of drug resistance for quantitative estimation of the phenotypic resistance outcomes (Khan et al, 2019). To systematically understand the effects (protein stability changes, flexibitliy drift, and protein ligand interaction) of these mutations, we performed in silico saturation mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mutants were generated at positions S324F, E325K, G341R, D342N, D343N, A344P, I351F, T370P, and W403G using PYMOL (DeLano, 2002). Free energy differences between MTs and WT RpsA from our previous papers (Khan et al, 2018c(Khan et al, , 2019bRehman et al, 2019) were re-analyzed. PZA is a prodrug, activated by MTB encoded pncA into POA, targeting RpsA.…”
Section: Mutants Selection In Rpsamentioning
confidence: 99%
“…WT exhibited a more stable state as compared to mutants. POA resistance might be due the GFE states altering the affinity of RpsA (Khan et al, 2019b).…”
Section: Nomentioning
confidence: 99%